2020
DOI: 10.1111/1475-6773.13574
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes collected in ambulatory oncology practices: Feasibility, patterns, and correlates

Abstract: Objective: To examine the feasibility of soliciting outcomes from adults who received chemotherapy treatment for cancer and describe the patterns and correlates of patient-reported toxicities. Data Sources: Patient survey data from 29 Michigan ambulatory oncology practices collected in 2017. Study Design: Secondary analysis of patient survey data. Descriptive statistics were generated at the patient and practice levels. Thematic analysis of open-text comments identified clusters of frequently reported toxiciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This can be problematic in supportive care. Ongoing studies are examining the feasibility of collecting patient-reported outcomes (PROMS), particularly in ambulatory patients [20 ▪ ]. With antiemetics, for example, measurements must include both nausea and vomiting, acute emesis over 24 h and delayed emesis often until 120 h. Even a popular and validated tool The MASCC Antiemesis Tool (MAT), which is an 8-item scale to assess post-chemotherapy nausea and vomiting with each cycle of chemotherapy does not record the duration of episodes of nausea and vomiting and does not assess anticipatory vomiting [21 ▪ ].…”
Section: Lack Of Standardized Outcome Measuresmentioning
confidence: 99%
“…This can be problematic in supportive care. Ongoing studies are examining the feasibility of collecting patient-reported outcomes (PROMS), particularly in ambulatory patients [20 ▪ ]. With antiemetics, for example, measurements must include both nausea and vomiting, acute emesis over 24 h and delayed emesis often until 120 h. Even a popular and validated tool The MASCC Antiemesis Tool (MAT), which is an 8-item scale to assess post-chemotherapy nausea and vomiting with each cycle of chemotherapy does not record the duration of episodes of nausea and vomiting and does not assess anticipatory vomiting [21 ▪ ].…”
Section: Lack Of Standardized Outcome Measuresmentioning
confidence: 99%
“…Evidence from a review suggests that overall survival (OS) is increasing for many cancers due to the availability of new cancer medicines [3]. However, evidence of the impact on patients' quality of life (QoL) has focused principally on chemotherapy toxicity and symptom management [4][5][6][7][8]. Less is known about the impact of cancer medicines more broadly on patients' lives; this is often an important consideration in the patient-clinician decision-making process.…”
Section: Introductionmentioning
confidence: 99%